Education efforts may contribute to wider acceptance of human papillomavirus self-sampling - Crofts V; Flahault E; Tebeu PM; Untiet S; Kengne Fosso G; Boulvain M; Vassilakos P; Petignat P (Dove Medical Press, 2015)
Victoria Crofts,1,* Emmanuel Flahault,1,* Pierre-Marie Tebeu,2 Sarah Untiet,3 Gisèle Kengne Fosso,2 Michel Boulvain,3 Pierre Vassilakos,4 Patrick Petignat3 1Faculty of Medicine, University of Geneva, Geneva, Switzerland; 2Department of Gynecology and Obstetrics, University Center Hospital, Yaoundé, Cameroon; 3Department of Gynecology and Obstetrics, Geneva University Hospitals, Geneva, Switzerland; 4Geneva Foundation for Medical Education and Research, Geneva, Switzerland *These authors contributed equally to this paper Background: Information about women’s acceptance of new screening methods in Sub-Saharan Africa is limited. The aim of this study was to report on women’s acceptance of human papillomavirus (HPV) self-sampling following an educational intervention on cervical cancer and HPV.Methods: Women were recruited from the city of Tiko and a low-income neighborhood of Yaoundé, both in Cameroon. Written and oral instructions about how to perform an unsupervised HPV self-sample were given to participants, who performed the test in a private room. Acceptability of HPV self-sampling was evaluated by questionnaire. Participants previously screened for cervical cancer by a physician were asked additional questions to assess their personal preferences about HPV self-sampling.Results: A sample of 540 women were prospectively enrolled in the study; median age was 43 years old (range 30–65 years). Participants expressed a high level of acceptance of HPV self-sampling as a screening method following information sessions about cervical cancer and HPV. Most expressed no embarrassment, pain, anxiety, or discomfort (95.6%, 87.8%, 91.3%, and 85.0%, respectively) during the information sessions. Acceptance of the method had no correlation with education, knowledge, age, or socio-professional class. Eighty-six women (16%) had a history of previous screening; they also reported high acceptance of HPV self-sampling.Conclusion: Educational interventions on cancer and HPV were associated with high acceptability of HPV self-testing by Cameroonian women. Further evaluation of the intervention in a larger sample and using a control group is recommended.Keywords: Cameroon women, cervical cancer screening, HPV, low-resource country, physician sampling, self-sampling